“That bastard chose me”: the use of metaphor in women’s cancer blogs - Kaja Kvaale; Oddgeir Synnes; Olaug S. Lian; Hilde Bondevik (Qualitative Research in Medicine & Healthcare, 2024)
Metaphors play a significant role in how cancer is experienced and discussed. This study delves into the utilization of metaphors by women bloggers grappling with colorectal and gynecological cancers. By focusing on cancer types less represented in mainstream media, we aim to shed light on cancer cultures associated with body areas often considered taboo. Our findings reveal that widely recognized expressions and stories about cancer, such as the metaphors of battle and narratives promoting optimism and heroism in the face of illness, are deeply ingrained. However, a notable discovery is the prevalence of personification alongside these conventional expressions. Personifying cancer endows it with human characteristics, providing an outlet for bloggers to express their fear and frustration, including articulating feelings of sadness and anger, diverging from narratives centered on heroism and positive thinking. Furthermore, our analysis reveals a significant emphasis on death, underscoring that despite advancements in treatment, bloggers still perceive cancer as highly lethal. Personification can serve both detrimental and therapeutic purposes for bloggers and for societal perceptions of cancer survivorship, both reinforcing and opposing dominant Western discourses surrounding the illness. These findings enrich our understanding of cognitive and cultural tools used to describe cancer within contemporary Western society.